2021
DOI: 10.1016/j.xphs.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bioavailability with Dry Powder Cannabidiol Inhalation: A Phase 1 Clinical Study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Devinsky et al 71 compared the pharmacokinetics of 50 mg oral CBD to 2.1 mg CBD delivered using dry powder inhaler technology. As expected, pulmonary delivery accelerated absorption and increased bioavailability of CBD compared to oral administration.…”
Section: Resultsmentioning
confidence: 99%
“…Devinsky et al 71 compared the pharmacokinetics of 50 mg oral CBD to 2.1 mg CBD delivered using dry powder inhaler technology. As expected, pulmonary delivery accelerated absorption and increased bioavailability of CBD compared to oral administration.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was quite difficult to justify a suitable daily dose [ 24 , [27] , [28] , [29] ]. In a recent phase 1 clinical study of CBD dry powder inhaler, the authors reported a C max of 18.78 ng/mL of CBD [ 30 ], and in general the lung drug concentration should be about 100-fold higher than the concentration in the plasma [ 31 ]. Also, it is worth noting that the extravascular lung fluid according to various reports is about 2–10 mL [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various oral CBD formulations are available, such as oil drops and oil in capsules [12]. However, oral CBD has demonstrated the lowest bioavailability of 6-19% compared to other delivery routes due to irregular absorption and extensive hepatic metabolism [15,16,133]. The high lipophilicity of CBD also contributes to poor and slow absorption as precipitation can occur in the gastrointestinal tract [14].…”
Section: Oral Administrationmentioning
confidence: 99%
“…The bioavailability of CBD depends on the route of administration [12]. CBD has low aqueous solubility (12.6 mg/L) and low bioavailability (4-20%) due to extensive first pass metabolism [13][14][15]. The poor oral bioavailability leads to low drug efficiency, hence a higher dose is required to reach the therapeutic concentration, which subsequently increases the risk of side effects and drug interactions [16].…”
Section: Introductionmentioning
confidence: 99%